2008
DOI: 10.1182/blood-2007-04-085787
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mouse LMIR5/CLM-7 as an activating receptor: differential regulation of LMIR5/CLM-7 in mouse versus human cells

Abstract: IntroductionIt is widely accepted that mast cells are major effector cells in allergic inflammation through a high-affinity IgE receptor (Fc⑀RI). However, recent advances have delineated the significant roles of mast cells in both innate and adaptive immune responses. [1][2][3][4] To find a novel immune receptor expressed on mast cells, we previously performed a signal sequence trap based on retrovirusmediated expression screening (SST-REX). 5 In this screening, we isolated a cDNA for a novel immune receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…Anti-CD300b antibody cross-linking promotes Syk, Erk and Akt phosphorylation via DAP12. 21 We found that, while Syk, Erk, PI3K and Akt phosphorylation in macrophages is induced upon apoptotic cell recognition, only Syk, PI3K and Akt phosphorylation are markedly impaired in CD300b-silenced macrophages. This indicates that, in response to apoptotic cell recognition, CD300b regulates PI3K activation via interaction with DAP12 and Syk, and that the PI3K pathway is the major signaling pathway used in CD300b-mediated phagocytosis.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…Anti-CD300b antibody cross-linking promotes Syk, Erk and Akt phosphorylation via DAP12. 21 We found that, while Syk, Erk, PI3K and Akt phosphorylation in macrophages is induced upon apoptotic cell recognition, only Syk, PI3K and Akt phosphorylation are markedly impaired in CD300b-silenced macrophages. This indicates that, in response to apoptotic cell recognition, CD300b regulates PI3K activation via interaction with DAP12 and Syk, and that the PI3K pathway is the major signaling pathway used in CD300b-mediated phagocytosis.…”
Section: Resultsmentioning
confidence: 67%
“…CD300b has a short intracellular domain without any known signaling motifs; 21 however it contains a positively charged lysine residue within its transmembrane segment, which could promote pairing with an appropriate adaptor molecule. 21 Both DAP10 and DAP12 have a negatively charged aspartic acid residue within their transmembrane domains making them suitable for pairing with CD300b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations